Heterogeneity of EGFR Aberrations and Correlation with Histological Structures: Analyses of Therapy‐Naive Isogenic Lung Cancer Lesions withEGFRMutation. Issue 10 (October 2016) - Suda, Kenichi; Murakami, Isao; Yu, Hui; Ellison, Kim; Shimoji, Masaki; Genova, Carlo; Rivard, Christopher J.; Mitsudomi, Tetsuya; Hirsch, Fred R.
ABSTRACT : Introduction: : EGFR gene somatic mutation is reportedly homogeneous. However, there are few data regarding the heterogeneity of expression of mutant EGFR protein and EGFR gene copy number, especially in extrathoracic lesions. These types of data may enhance our understanding of the biology of EGFR ‐mutated lung cancer and our understanding of the heterogeneous response patterns to EGFR TKIs. Methods: : An 81‐year‐old never‐smoking female with lung adenocarcinoma could not receive any systemic therapy because of her poor performance status. After her death, 15 tumor specimens from different sites were obtained by autopsy. Expression of mutant EGFR protein and EGFR gene copy numbers were assessed by immunohistochemical analysis and by silver in situ hybridization, respectively. Heterogeneity in these EGFR aberrations was compared between metastatic sites (distant versus lymph node) or histological structures (micropapillary versus nonmicropapillary). Results: : All lesions showed positive staining for mutant EGFR protein, except for 40% of the papillary component in one of the pulmonary metastases (weak staining below the 1+ threshold). Expression of mutant‐specific EGFR protein, evaluated by H‐score, was significantly higher in the micropapillary components than in the nonmicropapillary components (Mann‐Whitney U test, p = 0.014). EGFR gene copy number was quite different between lesions but not correlated with histological structure or metastatic form. However, EGFR gene copy numbers were similar between histological structures in each lesion. Conclusion: : These data indicate that expression of EGFR mutant protein and EGFR gene copy number do not change as a consequence of tumor progression. This also justifies using the biopsy specimens from metastases as a surrogate for primary tumors.